2021
DOI: 10.1155/2021/2227570
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Adsorption Mechanism of Graphene Oxide by Calcareous Sand in South China Sea

Abstract: To remove graphene oxide from wastewater, we used batch experiments with calcareous sand to recover GO. The adsorption properties and mechanisms of GO by calcareous sand were investigated by different characterization techniques. In this paper, the relationship between the coagulation of GO on calcareous sand and pH, calcareous sand content, GO initial concentration, and temperature was studied. The results show that calcareous sand can effectively adsorb GO from aqueous solution, the interaction of GO with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The results of other studies are summarized in Table 6 [ 63 , 64 , 65 ]. Due to factors such as insufficient theoretical knowledge and the limitations of experimental conditions, the study can also explore the adsorption properties of GO on different types of clay minerals.…”
Section: Discussionmentioning
confidence: 99%
“…The results of other studies are summarized in Table 6 [ 63 , 64 , 65 ]. Due to factors such as insufficient theoretical knowledge and the limitations of experimental conditions, the study can also explore the adsorption properties of GO on different types of clay minerals.…”
Section: Discussionmentioning
confidence: 99%
“…The graphene coating on the Au grating in this structure can make the energy more localized and prevent the metal from oxidation [ 21 25 ]. In addition, the dielectric constant of graphene has many similarities with metals, and when the imaginary part of the conductivity of graphene is greater than zero, the surface equipartition excitations in TM mode will be excited by the metallic nature exhibited by graphene and produce a strong field localization effect.…”
Section: Structural Modeling and Theoretical Analysismentioning
confidence: 99%
“…Based on a miscible displacement column experiment, Elbana and Selim [23] reported that the adsorption efficiency of Pb reached 99.5% withcalcareous soil. Lv et al [24] indicated that calcareous sand is a potential adsorbent for graphene oxide (GO), and the adsorption process significantly depends on pH value. Salzman et al [25] concluded that fluoride is adsorbed by calcareous and siliceous sand during drier summer months, whiledesorption occurs during rainy winter months.…”
Section: Introductionmentioning
confidence: 99%